Zanne Domoney-Lyttle: ’The Bible and Comics’; Assaf Gamzou and Ken Koltun-Fromm, eds.: ’Comics and Sacred Texts’ - Dillon, Amanda (Postscripts: The Journal of Sacred Texts, Cultural Histories, and Contemporary Contexts, 2025)
Zanne Domoney-Lyttle: The Bible and Comics: Women, Power and Representation in Graphic Narratives. Scriptural Traces: Critical Perspectives on the Reception and Influence of the Bible. London: Bloomsbury T&T Clark (2024) Assaf Gamzou and Ken Koltun-Fromm, eds.: Comics and Sacred Texts: Reimagining Religion and Graphic Narratives. Oxford, MS: University Press of Mississippi (2018)